PERAN PROJECT MANAGER, STRATEGIST, DAN EVENT MANAGER DALAM KAMPANYE KOMUNIKASI PEMASARAN DEBIURYN COSMETICS SEBAGAI PENGUATAN BRAND POSITIONING PADA REMAJA USIA 12–19 TAHUN DI KOTA SEMARANG - Dhita Dwi Nurhidayah; Djoko Setyabudi (Interaksi Online, 2026)
In the increasingly competitive skincare industry, DeBiuryn Cosmetics faces challengesrelated to low brand awareness (14.6%) and suboptimal product sales among adolescents inSemarang. This study explains the implementation of an integrated marketing communicationcampaign titled “Stay Bright, Stay Youth,” which aims to strengthen brand positioning andincrease consumer engagement through digital and offline strategies. The campaign utilizedIntegrated Marketing Communication (IMC) by combining digital activation through Instagramand TikTok, as well as experiential marketing activities such as DeBiuryn Class Out and Glow Onthe Booth. The evaluation results show a significant increase in brand awareness from 14.6% to84.8%, along with improved product sales exceeding the initial targets. This success demonstratesthat an integrated communication strategy effectively enhances brand visibility, strengthenspositioning, and drives consumer purchase behavior in the teenage skincare market